2020
DOI: 10.3390/ijerph17186587
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence in Outpatient Physician Clinics: A Systematic Review

Abstract: Workplace violence (WPV) has been extensively studied in hospitals, yet little is known about WPV in outpatient physician clinics. These settings and work tasks may present different risk factors for WPV compared to hospitals, including the handling/exchange of cash, and being remotely located without security presence. We conducted a systematic literature review to describe what is currently known about WPV in outpatient physician clinics. Six literature databases were searched and reference lists from includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
2
27
0
1
Order By: Relevance
“…A recent meta-analysis study with a total of 331,544 participants reported that the prevalence of WPV against healthcare workers was 61.9% ( 5 ). Some other review studies reported a wide range of the prevalence of WPV (9.5%−97.6%) among different kinds of HPs in different regions ( 6 8 ). The second achievement was about the adverse outcomes of WPV on HPs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis study with a total of 331,544 participants reported that the prevalence of WPV against healthcare workers was 61.9% ( 5 ). Some other review studies reported a wide range of the prevalence of WPV (9.5%−97.6%) among different kinds of HPs in different regions ( 6 8 ). The second achievement was about the adverse outcomes of WPV on HPs.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence (WPV) refers to an individual's or group's socially unacceptable, aggressive (and sometimes destructive) behavior ( 1 3 ). WPV against healthcare workers is a global public health problem that has been underreported and largely ignored ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a 2020 systematic review of studies on outpatient workplace violence conducted by survey and interviews with victims, violence was commonly attributed to clinic-based factors, such as unmet service needs, misunderstanding between patient and clinician, and overcrowding of the clinic or long wait times. 28 These findings suggest that addressing workplace violence strictly by directing security measures toward people with mental illness is misguided and, furthermore, that responses to inhumane and inadequate medical care may be pathologized as violence or mental illness. Of note, this review did not find a single study conducted in the United States, which draws attention to the fact that there is no evidence base for policing practices commonly employed in outpatient clinics in this country.…”
Section: Policing Outpatient Mental Healthmentioning
confidence: 99%